2003
DOI: 10.1002/cne.10874
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of doublecortin during adult neurogenesis

Abstract: During development of the central nervous system, expression of the microtubule binding protein doublecortin (DCX) is associated with migration of neuroblasts. In addition to this developmental role, expression of DCX remains high within certain areas of the adult mammalian brain. These areas, mainly the dentate gyrus and the lateral ventricle wall in conjunction with the rostral migratory stream and olfactory bulb, retain the capacity to generate new neurons into adulthood. Adult neurogenesis is typically det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
1,303
5
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,397 publications
(1,408 citation statements)
references
References 47 publications
93
1,303
5
7
Order By: Relevance
“…We found that the basal levels of cells incorporating BrdU in the hippocampus and SVZ of sham-operated control animals were consistent with those of previous reports (Kempermann and Gage, 2000;Mandairon et al, 2003;Brown et al, 2003;Yang et al, 2004). In the SVZ, BrdUpositive cells were concentrated in a tight band in the dorsal area (Figure 1a), and in a looser network of single cells in the ventral area.…”
Section: Resultssupporting
confidence: 92%
“…We found that the basal levels of cells incorporating BrdU in the hippocampus and SVZ of sham-operated control animals were consistent with those of previous reports (Kempermann and Gage, 2000;Mandairon et al, 2003;Brown et al, 2003;Yang et al, 2004). In the SVZ, BrdUpositive cells were concentrated in a tight band in the dorsal area (Figure 1a), and in a looser network of single cells in the ventral area.…”
Section: Resultssupporting
confidence: 92%
“…This is true for the dSVZ and extends up to the lesion core, where strong DCX upregulation can be seen. The expression of DCX, a marker for migrating neuronal progenitors, is an indication of neurogenesis as in the adult brain, within areas of continuous neurogenesis (Brown et al, 2003), or in case of increase in brain neurogenesis induced by environmental factors or insults (Couillard-Despres et al, 2005). Such an increase in neurogenesis following QA injection is in line with previous findings (Tattersfield et al, 2004;Collin et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…WBI decreased the density of DCX + , neurons in young adults, as previously reported (8,11,13), but had no effect on the density of DCX + cells in old rats ( Figure 2). One must be circumspect when interpreting the effects of a change or lack of change in the number of DCX + cells on neuronal replacement (34,(45)(46)(47); DCX is expressed in dividing neuroblasts and for approximately two weeks in differentiating, post-mitotic immature neurons (34,45) but not all DCX + neurons survive to maturity. Where examined in previous studies, however, WBI-induced decreases in neurogenesis in younger animals demonstrated by S-phase labeling with bromodeoxyuridine (BrdU) combined with neuron specific markers have been paralleled by decreases in DCX labeling (8,11).…”
Section: Discussionmentioning
confidence: 99%